Pengaruh Motivasi, Kreativitas, Inovasi dan, Digital Marketing terhadap Keberlanjutan Usaha pada Kafe Shop di Kecamatan Sumbersari Kabupaten Jember - Ilham Dwi Prasetya; Akhmad Suharto; Rusdiyanto Rusdiyanto (Jurnal Simki Economic, 2025)
This study began with the phenomenon of many businesses, including cafes, that could not survive long in the midst of fierce business competition. Due to a number of difficult challenges, many business owners decided to stop their businesses. Several factors that are suspected to be the main causes of this problem are lack of innovation, low creativity in product development, and less than optimal digital marketing. This study aims to analyze the impact of motivation, creativity, innovation, and digital marketing on the sustainability of cafe businesses in Sumbersari District, Jember Regency. The methodology applied in this study is quantitative, where data is collected through questionnaires and data analysis is carried out using multiple linear regression. The number of samples used is 125 respondents with the probability sampling method. The findings of the study indicate that motivation, creativity, innovation, and digital marketing have a significant influence on the sustainability of cafe businesses in Sumbersari District, Jember Regency.